Total factor productivity in Chinese manufacturing firms: the role of E-commerce adoption - Yu, W.; Du, B.; Guo, X.; Marinova, Dora (2023)
This paper seeks to investigate the relationship between e-commerce and total factor productivity (TFP) at the manufacturing firm level. Using data of 178 A-share listed companies in China during the period from 2015 to 2021, the article empirically tests the questions of whether and how e-commerce used directly by manufacturing firms can boost their productivity growth. The result shows that the penetration of e-commerce in manufacturing has a positive and significant effect on TFP growth. It is also found that the spillovers of intra-firm human capital and the effect of inter-firm market competition both play a crucial role in linking e-commerce to firm-level TFP growth. Specifically, e-commerce is beneficial to driving TFP growth significantly through attracting high-quality rather than low-quality human capital accumulating in manufacturing firms, as well as through improving appropriately market concentration rather than increasing the intensity of market competition. This article contributes to the existing literature by exploring the productivity-driving force of manufacturing firms which face transformation from a focus on the production to the marketing chain within the context of online business. It also provides policy applications how to improve the TFP of manufacturing firms through the use of digital platforms.